2021
DOI: 10.1186/s13054-021-03645-y
|View full text |Cite
|
Sign up to set email alerts
|

Early individualized positive end-expiratory pressure guided by electrical impedance tomography in acute respiratory distress syndrome: a randomized controlled clinical trial

Abstract: Background Individualized positive end-expiratory pressure (PEEP) by electrical impedance tomography (EIT) has potential interest in the optimization of ventilation distribution in acute respiratory distress syndrome (ARDS). The aim of the study was to determine whether early individualized titration of PEEP with EIT improved outcomes in patients with ARDS. Methods A total of 117 ARDS patients receiving mechanical ventilation were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…They also concluded that if the study population doubled and the intergroup mortality remained unchanged, the mortality of the PEEP group titrated according to the regional compliance would be significantly lower. Recently, Hsu et al ( 9 ) and He et al ( 10 ) reported that PEEP titrated by the regional C rs method can reduce mortality when compared with traditional methods in adult patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also concluded that if the study population doubled and the intergroup mortality remained unchanged, the mortality of the PEEP group titrated according to the regional compliance would be significantly lower. Recently, Hsu et al ( 9 ) and He et al ( 10 ) reported that PEEP titrated by the regional C rs method can reduce mortality when compared with traditional methods in adult patients with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reviews have summarized the applications of EIT in the treatment of adult ARDS ( 7 , 8 ). Two randomized controlled studies indicated that EIT-guided PEEP titration may reduce ARDS mortality ( 9 , 10 ). In terms of children, Rosemeier et al reported that during lung recruitment and PEEP titration, EIT could help to minimize regional alveolar overdistension and collapse and improve oxygenation ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, this study showed that the best PEEP was 5 cmH 2 O in a third of enrolled severe ARDS patients treated with ECMO. Finally, in a large randomized, open label, controlled trial comparing an EIT-based PEEP selection versus a low PEEP-FiO 2 table, the authors concluded in no difference in PEEP levels, oxygenation, and clinical outcome [ 36 ]. Taken together, these results clearly demonstrate that the priority is PEEP individualization in these patients.…”
Section: Lung Imaging and Clinical Managementmentioning
confidence: 99%
“…Similarly, recruitable alveolar collapse (CL) can be estimated at lower PEEPs against the best pixel compliance. Previous randomized controlled trials (total n > 200) suggested that PEEP titration using OD and CL information resulted in better clinical outcomes ( He et al, 2021 ; Hsu et al, 2021 ). The limitations of the method were discussed in a previous study ( Zhao et al, 2020 ) and considered in the clinical practice.…”
Section: Eit Data Acquisitionmentioning
confidence: 99%
“…EIT generates cross-sectional images of the impedance distribution within the thorax and measures continuously regional lung volume changes at the bedside ( Hinz et al, 2003 ; Kotani et al, 2016 ; Aguirre-Bermeo et al, 2018 ; Holanda et al, 2018 ). EIT is widely used in lung ventilation assessment in hypoxemia patients, including the PEEP titration (Dalla Corte et al, 2020 ; He et al, 2021 ; He et al, 2020 ; Yun et al, 2016 ; Becher et al, 2021 ; Gibot et al, 2021 ; Muders et al, 2021 ; Scaramuzzo et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%